Revisiting the Regulatory Framework of Capital Markets in Malaysia - Low, Chee Keong (Columbia Journal of Asian Law, 2001)
The structure of any financial system has one principal aim: to facilitate an effective use of funds. It is therefore important in the study of financial markets to understand where the funds come from and which sectors they pass through en route to their ultimate application within an economy. The sources of funds are savings in both the private and public sectors as well as the net inflow of funds from abroad. These are collectively channeled through intermediaries such as banks, provident and insurance funds, corporations, government agencies, and foreign institutions to generate a return that is commensurate with the risks taken on the investment. The latter represents the use of the funds that would generally fall into four categories, namely, private sector investments, public sector investments, accumulation of international reserves and unidentified private sector payments abroad. The last of the four would include remittances overseas for purposes of education and the maintenance of household expenditure. The diagram on the following page aptly illustrates this “stock” and “flow” concept of financial systems.1 Issuers of securities are legal persons; the companies issuing those securities. As a separate legal entity, a company enjoys a number of rights, including that of raising capital. Securities, unlike goods, are created rather than produced. They have no intrinsic value and are merely chose in action, namely, legally enforceable rights or interests in something else. They convey upon their holders an interest either as owners or creditors of the issuer.